2011
DOI: 10.1021/la203542x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of ZnO Nanoparticles at Circumneutral pH: A Study of Size Effects in the Presence and Absence of Citric Acid

Abstract: Understanding size-dependent processes, including dissolution, of engineered nanoparticles is essential in addressing the potential environmental and health impacts of these materials as well as their long-term stability. In this study, experimental measurements of size-dependent dissolution of well-characterized zinc oxide (ZnO) nanoparticles with particle diameters in the range of 4 to 130 nm have been measured at circumneutral pH (pH 7.5) and compared. Dissolution was found to be enhanced with smaller ZnO n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
250
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(283 citation statements)
references
References 57 publications
20
250
3
3
Order By: Relevance
“…The release of Zn 2+ by Nanosun and in-house synthesised ZnO particles has been studied in a previous paper. It has been shown that the extent of Zn 2+ release is dependent on the ZnO primary particle size [19,48]. This is commensurate with the classical predictions from the Kelvin equation relating solubility to the curvature of the particle.…”
Section: Resultssupporting
confidence: 72%
“…The release of Zn 2+ by Nanosun and in-house synthesised ZnO particles has been studied in a previous paper. It has been shown that the extent of Zn 2+ release is dependent on the ZnO primary particle size [19,48]. This is commensurate with the classical predictions from the Kelvin equation relating solubility to the curvature of the particle.…”
Section: Resultssupporting
confidence: 72%
“…Kinetics studies have shown that ZnO ENPs (at pH 7.5) can reach dissolution steady state in 24 hours [49]. However, in our study (pH 8.2), stable testing conditions were not reached until 48 hour aging, revealing clear dose-response relationships ( Figure 3) which corresponded to the increase in dissolution (Supplemental Data, Table S3).…”
Section: Influence Of Nom and Aging On Acute Toxicity Of Zno Enp Towacontrasting
confidence: 56%
“…The amorphous ZnO was considered to be an amorphous Zn(OH) 2 coating formed via hydrolysis of ZnO. 15 This amorphous Zn(OH) 2 was slightly soluble and Zn 2+ ions were released into solution. 12 Aqueous PO 4 3− can be adsorbed on the hydroxylation surface via exchange with OH − , forming an amorphous Zn phosphate layer.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…9−12 Some recent studies have also investigated interactions between NPs and natural organic matter (NOM), taking into consideration their ubiquity in the environment together with their high reactivity, 13 and the results have shown that dissolved NOM can enhance the stability and dissolution of NPs in water. 14,15 Nevertheless, we are still far from understanding the influence of environmental factors on the behavior of NPs in the natural environment. Many other important components such as phosphates are also present in addition to NOM, and these may interact with NPs and affect their behavior and fate.…”
Section: ■ Introductionmentioning
confidence: 99%